PENGARUH CORPORATE GOVERNANCE DAN STRUKTUR MODAL TERHADAP PROFITABILITAS (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Mohamad Faathir Al Hakim; Nila Firdausi Nuzula (Jurnal Administrasi Bisnis, 2018)
Global business competition is needed as a producer of high profit or optimum profit and increased prosperity for shareholders. Efforts to improve shareholder’s prosperity, found that difference of interest between the manager of the company called agent with the investor and shareholders that they called principals to execute business management. This difference of interst is called agency problem. The way to solved the conflict of agency problem needed the existence of good corporate governance. The context of implementation of Good Corporate Governance mechanism is still often found the existence of cheating or called(fraud), especially fraud on financial statements that result in information asymetry including get profitability. The companies in getting profitability also influenced by capital structure condition. This research attempts to identify the influence of Corporate Governance which is proxied by independent variabel Proportion of Board of Commisioners Independent(X1), Board of Directors(X2), Audit Committee(X3), Institutional Ownership(X4), and concept of Capital Structure which is proxied by independent variable Debt To Asset Ratio(X5) and Debt To Equity Ratio(X6) to concept of profitability which is proxied by dependent variable Return On Asset(Y1) and Return On Equity(Y2). Kеywords: Proportion of Board of Commisioners Independent, Board of Directors, Audit Committee, Institutional Ownership, Debt to Asset Ratio, Debt to Equity Ratio, Return On Asset, dan Return On Equity. АBSTRАK Persaingan bisnis secara global dibutuhkan sebagai penghasil laba optimum atau laba yang tinggi dan peningkatan kesejahteraan bagi pemegang saham. Upaya dalam peningkatan kesejahteraan pemegang saham (shareholder), ditemukan perbedaan kepentingan antara pihak pengelola perusahaan (agent) dengan pihak pemodal dan pemegang saham (principals) dalam menjalankan aktivitas pengelolaan usaha. Perbedaan kepentingan ini disebut dengan agency problem. Cara untuk mengatasi terjadinya konflik tersebut maka dibutuhkan adanya tata kelola perusahaan yang baik (Good Corporate Governance). Konteks penerapan mekanisme GCG masih sering ditemukan adanya kecurangan  (fraud), terutama kecurangan pada laporan keuangan yang mengakibatkan asimetri informasi termasuk pada perolehan profitabilitas. Perolehan profitabilitas juga dipengaruhi oleh kondisi struktur modal perusahaan. Penelitian ini bertujuan untuk mengetahui pengaruh konsep Corporate Governance yang diproksikan oleh variabel Proporsi Dewan Komisaris Independen (X1), Dewan Direksi (X2), Komite Audit (X3), Kepemilikan Institusional (X4) dan konsep Struktur Modal yang diproksikan oleh Debt To Asset Ratio (X5) dan Debt To Equity Ratio (X6) sebagai variabel independen terhadap konsep profitabilitas yang diprosikan oleh variabel dependen Return On Asset (Y1) dan Return On Equity (Y2). Kаtа Kunci: Proporsi Dewan Komisaris Independen, Dewan Direksi, Komite Audit, Kepemilikan Institusional, Debt to Asset Ratio, Debt to Equity Ratio, Return On Asset, dan Return On Equity.